FIGHT AGAINST NOISE AND VIBRATION IN INDUSTRIAL BUILDINGS - Turdiboyev Lochinbek Xolmirzo o’g’li; Botirov Bektosh Farhod o’g’li (American Journals Publishing, 2022)
Annotation: this article provides descriptions of sources of noise in industrial premises, the level and spectral composition of noise, measures to reduce noise.
Keywords: noise sources, noise level, noise reduction methods.